PERAN ORANGTUA DALAM MENGEMBANGKAN KECERDASAN SPIRITUAL REMAJA - Tibo, Paulinus; Simanullang, Melda Makrina; Tarigan, Thomas N. (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2022)
Many parents do not understand their role in the educational process to develop adolescent spiritual intelligence. Parents who are so busy with their daily routines that their role is starting to diminish, begin to leave teaching and religious, ethical and moral values to their children because they are considered time-consuming and more focused on their children's needs on other aspects of needs such as food, clothing and shelter. stay. This study aims to determine the role of parents in developing adolescent spiritual intelligence and to determine the development of adolescent spiritual intelligence. This study uses a qualitative approach, with techniques of observation, interviews and documentation. The target of this research is parents and teenagers in the Stasi St. Petrus Panombean. The results of the research described show that the role of parents has been carried out quite well in developing adolescent spiritual intelligence, namely guiding children to find the meaning of life, developing five important exercises, involving children in worship, enjoying natural scenery, visiting grieving relatives, educating spiritually through stories, increase spiritual intelligence with patience and gratitude. The form of the development of adolescent spiritual intelligence is a flexible or flexible life attitude in dealing with problems, a high level of intelligence, such as the ability to deal with problems, the ability to face fear, have vision and values, are reluctant to do something that causes harm, have the ability to see the relationship between things, and want to ask why and what.